The Port Elizabeth disturbances of October, 1920 - Baines, Gary F, 1955- (Rhodes University, Faculty of Humanities, Department of History, 1988)
Chapter one suggests thet trade and merchant capital, which were crucial to Port Elizabeth's economic development during the nineteenth century, was subsumed by the rise of manufactures and industrial capital after the First World War. Industrial expansion was cut short by the post-war recession, which caused un- and underemployment. The black worker, who experienced a severe loss in real earnings on account of the increased cost of living, became involved in a struggle with employers for wage increases. Chapter two shows how the policy of segregation was applied in Port Elizabeth, which meant that the workers were subjected to an increasing degree of control and regulation of their daily lives. The conditions of reproduction in the black townships fostered inter-racial and cross-class mobilisation which culminated in the formation of a general labour union, the Port Elizabeth Industrial and Commercial Workers' Union (PEICWU). Chapter three will suggest links between the tradition in Port Elizabeth of worker resistance and the unionisation of black workers in the post-war period. Thus, the first three chapters attempt to provide a historical perspective for analysing the underlying causes of the 1920 Port Elizabeth disturbances. The immediate cause of the disturbances was the arrest of the Union leader, Masabalala, after he called for a general strike. Chapter four will show how the intervention of the local authorities provoked a spontaneous act of defiance on the part of Union members. A demonstration outside the Baakens Street Police Station to demand the release of Masabalala, precipitated the tragic shootings of 23 October 1920. The repressive violence which left 22 dead (with two further deaths resulting indirectly from the incident) was unprecedented in South African history. The resolution of the crisis brought the workers no nearer to obtaining a reasonable settlement of the wage issue. If anything, the resolve of employers to deny wage demands was hardened by the actions of the local authorities, who attributed the disturbances to ' agitation '. Such thinly-disguised justifications of the shootings by the dominant classes, however, provoked recriminations from other quarters. Chapter five examines the legal and political ramifications of the Port Elizabeth shootings. The circumstances of the shootings prompted the Smuts Government to appoint a Commission of Enquiry in the face of public pressure. The Commission found that the Police and vigilantes were largely to blame for the high death toll. But the Government's 'whitewash' of the findings could not absolve the Police from culpability entirely, nor could it sidestep its own responsibility and liability to victims of the shootings. Finally, in Chapter six, an attempt will be made to assess the long term impact of the shootings on the PElCU and the black labour movement in Port Elizabeth generally. The outcome of the episode was a victory for employers, which dealt a body blow to worker organisation which only became resurgent in the 1950s.
Keywords: Black people -- South Africa -- Port Elizabeth -- Social conditions; Police shootings -- South Africa -- Port Elizabeth; Labor movement -- South Africa -- Port Elizabeth -- History